Comparison of organic versus mineral resource effects on short-term aggregate carbon and nitrogen dynamics in a sandy soil versus a fine textured soil - Chivenge, Pauline P.; Vanlauwe, Bernard; Gentile, R; Six, Johan (Elsevier, 2011)
Aggregation and stabilization of soil organic C (SOC) and N are highly dependent on soil texture and addition of organic resources (ORs). While OR quality may influence SOC and N stabilization within aggregates, the simultaneous addition of N-fertilizers may enhance OR decomposition resulting in loss of SOC. A mesocosm study was conducted on a clayey soil at Embu and a sandy soil at Machanga in central Kenya to determine the influence of soil texture, OR quality and N-fertilizer on aggregation, SOC and N. Tithonia diversifolia (high quality), Calliandra calothyrsus (medium quality) and Zea mays (maize; low quality) residues, natural abundance or labeled with 15N, were applied to soil at an equivalent rate of 4 Mg C ha?1 compared to no input control. Each treatment was fertilized with 120 kg 14N or 15N ha?1 as (NH2)2CO, or not fertilized. Soil samples were collected at installation of the mesocosms (start), and 8 months after installation (end). Soils were separated into different aggregate size fractions by wet sieving and macroaggregates were further fractionated to isolate microaggregates-within-macroaggregates. Total soil and aggregate fractions were analyzed for SOC and N. On average, 20% and 70% of SOC and N was in the macroaggregates in the sandy and clayey soils, respectively. There were no differences among OR quality in both soils but in the clayey soil all ORs resulted in greater SOC and N than in the control. However, proportions of OR-derived N in the macroaggregates, mostly in the microaggregates-within-macroaggregates were greater with sole applied maize in the clayey soil. The addition of N-fertilizer together with maize stover reduced soil N, macroaggregate N, and OR-derived N in the microaggregate and silt and clay fractions within macroaggregates compared to when maize was applied alone. In the sandy soil, Calliandra resulted in greater OR-derived N than Tithonia in the coarse particulate organic matter (cPOM; i.e., 5% compared to 2% of N applied). Thus, the greater polyphenol concentration in Calliandra likely slowed its decomposition compared to that of Tithonia. In addition, greater proportions of N and residue-derived N in the macroaggregates were observed in the coarse POM in the sandy soil whereas in the clayey soil it was in the microaggregates-within-macroaggregates. We conclude that the preservation of OR-derived N is affected by the chemical recalcitrance of the residues in sandy soils, whereas macroaggregate protection, and not OR quality, is the major factor in clayey soils.